O espaço de jogo no Drama: práticas pedagógicas a partir do tropicalismo - Alexandre Luiz Porto Junior (2024)
ABSTRACT: This article aims to contribute to the development of research in art education from the perspective of theater in the language of process drama (Cabral, 2006) as a teaching methodology. To this end, I reflect on the game (Huizinga, 2000) and the shared space of action (Sofia, 2012), together with the idea of experience (Larossa Bondía, 2002). Furthermore, I present the game as a concept that permeates interactions between beings, in an activity often considered idle, but which brings with it a power of exchange of knowledge and meanings between the agents involved. KEYWORDS: art education; dramatics; process drama.